2018
DOI: 10.2174/1874285801812010116
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Study of Quinolone Resistance Determining Regions of gyrA Gene and parC Genes in Clinical Isolates of Acintobacter baumannii Resistant to Fluoroquinolone

Abstract: Introduction: Acinetobacterb aumannii (A. baumannii) is an important pathogen in health care associated infections. Quinolone resistance has emerged in this pathogen.Aims & Objectives:The aim of the present study was to determine the presence of mutations of gyrA gene and parC genes by Restriction Fragment Length Polymorphism Polymerase Chain Reaction (RFLP-PCR) among clinical isolates of A. baumanii.Materials and Methods:The study was carried out on 140 clinical isolates of A. baumannii. The isolates were sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
14
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 27 publications
6
14
1
1
Order By: Relevance
“…These results differed from Stone et al [24], who reported that disc diffusion technique turned into a great fast screening technique to MIC for detection of antimicrobial sensitivity. Our results were matching with Maysaa et al and Valentine et al [25,26].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These results differed from Stone et al [24], who reported that disc diffusion technique turned into a great fast screening technique to MIC for detection of antimicrobial sensitivity. Our results were matching with Maysaa et al and Valentine et al [25,26].…”
Section: Discussionsupporting
confidence: 94%
“…The mixed mutations in those genes are related to remarkable decrease binding affinity for quinolones in the resistant organisms. Theses outcomes had been in settlement with Maysaa et al and Redgrave et al [25,27].…”
Section: Discussionmentioning
confidence: 86%
“…Quinolone resistance occurs via three different mechanisms: (i) target mutations in gyrase and topoisomerase IV, which weaken the respective quinolone–enzyme interactions; (ii) plasmid-borne resistance mediated by Qnr proteins, the AMEs AAC(6′)-Ib-cr and AAC(6′)-Ib-cr5, and by plasmid-encoded efflux pumps; and (iii) chromosome-derived resistance resulted by either low expression of porins or overexpression of chromosome-encoded efflux pumps [ 123 , 124 , 125 ]. A recent review reported resistance of A. baumannii to fluoroquinolones between 50% and 73% of cases, while the respective resistance in developing countries during the last years displayed a marked increase reaching 75% to 97.7% [ 98 , 126 ]. Table 4 lists all recorded quinolone-specific resistance mechanisms for A. baumannii.…”
Section: Resistance To Fluoroquinolonesmentioning
confidence: 99%
“…Although a single point mutation in DNA gyrase is usually not enough for resistance to fluoroquinolones in A. baumannii (maybe only against levofloxacin; single parC mutations link with ciprofloxacin resistance), concurrent mutations within QRDR regions of the gyrA and parC genes are linked with significantly higher level of quinolone resistance [ 130 , 131 ]. Alterations in gyrB and parE genes are of minor significance [ 126 ].…”
Section: Resistance To Fluoroquinolonesmentioning
confidence: 99%
“…These mutations are sequential, as primary mutations in gyrA81 are followed by mutations in parC88 and parC84 in A. baumannii. However, a study described strains carrying mutations in only the parC gene, revealing the involvement of other resistance mechanisms for fluoroquinolone 23 - 24 .…”
Section: Overview Of a Baumannii Antibiotic Resismentioning
confidence: 99%